2018
DOI: 10.1002/jctb.5863
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen removal by a metal‐resistant bacterium, Pseudomonas putida ZN1, capable of heterotrophic nitrification–aerobic denitrification

Abstract: BACKGROUND Bacteria capable of heterotrophic nitrification–aerobic denitrification have received increasing attention, and can achieve simultaneous nitrification and denitrification processes to accelerate nitrogen removal rate. However, heavy metals in industrial wastewater seriously affect the nitrogen removal by these bacteria. Thus, this work focused on the nitrogen removal ability of a metal‐resistant bacterium Pseudomonas putida ZN1. RESULTS ZN1 effectively removed ammonium, nitrate and nitrite with maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(12 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…As is shown in figure 4, the amount of GO added has no effect on the intermediates of heterotrophic nitrification. Almost no accumulation of nitrite, nitrate or other intermediates occurs throughout the whole heterotrophic nitrification process, which is consistent with results found for Pseudomonas putida ZN1 [27] and Klebsiella sp. TN-10 [28].…”
Section: Effect Of Different Doses Of Graphene Oxide In Polyvinyl-alcsupporting
confidence: 91%
“…As is shown in figure 4, the amount of GO added has no effect on the intermediates of heterotrophic nitrification. Almost no accumulation of nitrite, nitrate or other intermediates occurs throughout the whole heterotrophic nitrification process, which is consistent with results found for Pseudomonas putida ZN1 [27] and Klebsiella sp. TN-10 [28].…”
Section: Effect Of Different Doses Of Graphene Oxide In Polyvinyl-alcsupporting
confidence: 91%
“…and Pseudomonas taiwanensis using glucose. Zhang et al () studied the effect of different C/N ratios and concluded that the C/N ratio of 16 with citrate as the carbon source was most conducive for nitrogen removal, which is much higher than other heterotrophs. This suggests that these species can be used in wastewater treatment plant with high organic loads.…”
Section: Environmental Factors Affecting Denitrificationmentioning
confidence: 99%
“…Metal‐resistant Pseudomonas putida with nitrogen removal ability was isolated from the coking industry (Zhang et al ). It showed high capacity for nitrogen removal and high tolerance to metal ions.…”
Section: Aerobic Denitrification In the Presence Of Metal Ionsmentioning
confidence: 99%
“…To date, bacteria with this capability has been found extensively, namely Pseudomonas putida ZN1, Vibrio diabolicus SF16, Pseudomonas stutzeri YG‐24, Zobellella taiwanensis DN‐7 and Cupriavidus sp. S1 . The high total nitrogen (TN) removal efficiency of above 90% was usually obtained under aerobic condition.…”
Section: Introductionmentioning
confidence: 99%
“…S1. [4][5][6][7][8] The high total nitrogen (TN) removal efficiency of above 90% was usually obtained under aerobic condition. Given these positive characteristics, they serve as a promising alternative for other traditional wastewater nitrogen removal processes.…”
Section: Introductionmentioning
confidence: 99%